High Mobility Group Box 1 and Heat Shock Protein-70 Expression Post (-)-Epigallocatechin-3-Gallate in East Java Green Tea Methanolic Extract Administration During Orthodontic Tooth Movement in Wistar Rats - Alexander Patera Nugraha; Ida Bagus Narmada; Putri Intan Sitasari; Fidiyah Inayati; Rahendra Wira; Ari Triwardhani; Thalca Hamid; I Gusti Aju Wahju Ardani Ardani; Irwadi Djaharu'ddin; Dwi Rahmawati; Regina Purnama Dewi Iskandar (Association of Support to Oral Health Research (APESB), 2022)
Objective: To investigate the expression of High Mobility Group Box 1 (HMGB1) and Heat Shock Protein-70 (HSP-70) during orthodontic tooth movement (OTM) after (-)- Epigallocatechin-3-Gallate (EGCG) in East Java Green Tea (Camelia Sinensis) Methanolic Extract (GTME) administration in vivo. Material and Methods: 28 Wistar rats (Rattus Novergicus) was used and divided into 4 groups accordingly: K- without EGCG and OTM; K+ with OTM, without EGCG for 14 days; T1with OTM for 14 days and EGCG for 7 days; treatment group 2 (T2) with OTM and EGCG for 14 days. OTM animal model was achieved through the installation of the OTM device by means of NiTi close coil spring with 10g force placed between the first incisor and first maxillary molars. The samples were terminated on Day 14. The pre-maxillary was isolated for the immunohistochemical examination. Analysis of Variance (ANOVA) then continued with Tukey Honest Significant Difference (HSD) (p<0.05) was performed to analyze the data. Results: The highest HMGB1 and HSP-70 expression were found in the K+ group pressure  side, meanwhile the lowest HMGB1 and HSP-70 expression were found in K- group tension side in the alveolar bone. There was a significant decrease of HMGB1 and HSP-70 expression in T2 compared to T1 and K+ with significant between groups (p<0.05; p=0.0001). Conclusion: The decreased expression of HMGB1 and HSP-70 in alveolar bone of OTM wistar rats due to post administration of GTME that consisted EGCG.